From Molecular Therapies to Lysosomal Transplantation and Targeted Drug Strategies: Present Applications, Limitations, and Future Prospects of Lysosomal Medications - Adel A. Alhowyan; Gamaleldin I. Harisa (Biomolecules)
Lysosomes are essential intracellular organelles involved in plentiful cellular processes such as cell signaling, metabolism, growth, apoptosis, autophagy, protein processing, and maintaining cellular homeostasis. Their dysfunction is linked to various diseases, including lysosomal storage disorders, inflammation, cancer, cardiovascular diseases, neurodegenerative conditions, and aging. This review focuses on current and emerging therapies for lysosomal diseases (LDs), including small medicines, enzyme replacement therapy (ERT), gene therapy, transplantation, and lysosomal drug targeting (LDT). This study was conducted through databases like PubMed, Google Scholar, Science Direct, and other research engines. To treat LDs, medicines target the lysosomal membrane, acidification processes, cathepsins, calcium signaling, mTOR, and autophagy. Moreover, small-molecule therapies using chaperones, macro-therapies like ERT, gene therapy, and gene editing technologies are used as therapy for LDs. Additionally, endosymbiotic therapy, artificial lysosomes, and lysosomal transplantation are promising options for LD management. LDT enhances the therapeutic outcomes in LDs. Extracellular vesicles and mannose-6-phosphate-tagged nanocarriers display promising approaches for improving LDT. This study concluded that lysosomes play a crucial role in the pathophysiology of numerous diseases. Thus, restoring lysosomal function is essential for treating a wide range of conditions. Despite endosymbiotic therapy, artificial lysosomes, lysosomal transplantation, and LDT offering significant potential for LD control, there are ample challenges regarding safety and ethical implications.